To solve the equation
\[ (x + 7)^2 (x - 2)(4x - 7) = 0, \]
we will set each factor equal to zero and solve for \(x\).
-
First, set \((x + 7)^2 = 0\):
\[ (x + 7) = 0 \implies x = -7. \]
Since it is a squared term, \(x = -7\) is a double root.
-
Next, set \((x - 2) = 0\):
\[ x - 2 = 0 \implies x = 2. \]
-
Finally, set \((4x - 7) = 0\):
\[ 4x - 7 = 0 \implies 4x = 7 \implies x = \frac{7}{4}. \]
Now, we can summarize the solutions:
- From \((x + 7)^2=0\): \(x = -7\) (double root)
- From \((x - 2)=0\): \(x = 2\)
- From \((4x - 7)=0\): \(x = \frac{7}{4}\)
Thus, the complete set of solutions to the equation is:
\[ x = -7, 2, \frac{7}{4}. \]
So the final answer is:
\[ -7, 2, \frac{7}{4} \]
(You can enter this as: -7, 2, 7/4).